Art Music by Caribbean Composers: Martinique - Gangelhoff, Christine; LeGrand, Cathleen (International Journal of Bahamian Studies, 2013)
Along with its political affiliation, the island maintains cultural ties to France. French is the official language and Creole is also widely spoken (Cyrille, 2008). The “dance repertoire of nineteenth-century French ballrooms” influenced the local styles of music in Martinique (Cyrille, 2005, para. 3). “French contradances, waltzes, polkas and mazurkas were frequently played by bands composed of black musicians who gave them a new twist. They evolved into the Creole waltz, the polka and the mazouk” (Cyrille, 2005, para. 3). The biguine is another musical genre native to Martinique but inspired by French ballroom music. “Characterized by a lively 2/4 meter and an eight-bar structure, the biguine merges rhythmic elements of African origin with European-style harmony” (Cyrille, 2005, para. 3). Other musical styles, such as mazonn and bélé, were inspired by the African heritage of Martinique. Casinos and ballrooms with entry fees, long provided popular performance venues for local musicians (Cyrille, 2005).